The second language acquisition of past tense marker in English by L1 speakers of chinese. - Sharmini, Sharon; Kelly Tee, Pei Leng; Singaram, Nallammai; Jusoff, Kamaruzaman (2009)
This study is considered the L2 acquisition and underlying of past tense marker, focusing on whether or not L2 learners of English are successful in associating the grammatical properties with Chinese language. Although the dataset is small, the results showed that Chinese speakers are able to acquire the past-tense marker although Chinese language has none of this feature. The L1 Chinese speakers are able to acquire the regular past-tense marker better co mpared to the irregular form.